Can Intraoperative Low-Dose R,S-Ketamine Prevent Depressive Symptoms After Surgery? The First Meta-Analysis of Clinical Trials - Pang, Liwei; Cui, Meiying; Dai, Wanling; Kong, Jing; Chen, Hongzhi; Wu, Shuodong (Frontiers in Pharmacology, 2020)
Background Post-operative depression is a common complication after surgery that profoundly affects recovery and prognosis. New research indicates that (R,S)-ketamine is a potent anti-depressant that exerts a rapid and sustained anti-depressive effect. However, there is no consensus on whether intraoperative low-dose (R,S)-ketamine prevents post-operative depression. Objectives This study aimed to investigate the safety, feasibility, and short-term complications of intra-operative low-dose (R,S)-ketamine in preventing post-operative depressive symptoms. Methods The Web of Science, Cochrane, PubMed, and CNKI databases were systematically searched (last search 2020-2-28) to identify studies involving ketamine. Sensitivity and meta-regression analyses were performed to identify potential confounders. The meta-analysis was performed using Review Manager 5.3. Results A total of 13 studies (7 in Chinese and 6 in English) representing 1148 cases of patients who were treated with (R,S)-ketamine and 874 cases of patients who received other treatments were included in the meta-analysis. Anesthesia duration and blood loss did not significantly differ between the two groups, demonstrating that (R,S)-ketamine was safe (OR: 0.27; 95% CI: -1.14–1.68; P = 0.71) for prophylactic treatment of post-operative depression. Blood loss (OR: -1.83; 95% CI: -8.34–4.68; P = 0.58), the number of post-operative depressive patients (95% CI: 0.8–1.07; P = 0.08; (R,S)-ketamine: control = 12.9%:15.8%), and postoperative complications (OR: 0.83, 95% CI: 0.44–1.58; P = 0.57; (R,S)-ketamine: control = 19.3%:19.3%) were all similar across groups.Intra-operative low-dose (R,S)-ketamine reduced extubation time (OR: -2.84; 95% CI: -5.48–-0.21; P = 0.03). Conclusions The prophylactic anti-depressant effect of (R,S)-ketamine did not significantly differ between the (R,S)-ketamine and control groups in patients undergoing general or spinal anesthesia. However, (R,S)-ketamine use led to a higher incidence of adverse reactions in patients under 40 years of age who underwent a Cesarean section under spinal anesthesia.